Multi-solitons in the model of an inhomogeneous optical fiber - Jinfang Li; Chunjiang Wang; Li Zhang; Jian Zhang (AIMS Mathematics)
This paper was concerned with the inhomogeneous optical fiber model, which was governed by a nonlinear Schrödinger equation with variable coefficients. By spectral analysis for Lax pair of the equation, a corresponding Riemann-Hilbert problem was formulated. By solving the Riemann-Hilbert problem with simple poles, the formula of multi-soliton solutions was derived. Finally, we considered a soliton control system and obtained the one-soliton and two-soliton.